Chronic oscillating glucose challenges disarrange innate immune homeostasis to potentiate the variation of neutrophil–lymphocyte ratio in rats with or without hidden diabetes mellitus - Yang G (Dove Medical Press, 2018)
Gaoxiong Yang,1* Rui Yan,2* Huanjun Tong,3* Jitai Zhang,1 Bin Chen,4 Xiangyang Xue,5 Jue Wang,6 Maoping Chu,7 Shengwei Jin,8 Ming Li1 1Cardiac Regeneration Research Institute, Wenzhou Medical University, Wenzhou, China; 2School of Laboratory Medicine and Life Science, Wenzhou Medical University, Wenzhou, China; 3The Second Clinical Medical College, Wenzhou Medical University, Wenzhou, China; 4Department of Medical Ultrasound, The First Affiliated Hospital of Wenzhou Medical University, Wenzhou, China; 5Department of Microbiology and Immunology, Institute of Molecular Virology and Immunology, Institute of Tropical Medicine, Wenzhou Medical University, Wenzhou, China; 6Department of Cardiac Surgery, The First Affiliated Hospital of Wenzhou Medical University, Wenzhou, China; 7Children’s Heart Center, The Second Affiliated Hospital and Yuying Children’s Hospital, Institute of Cardiovascular Development and Translational Medicine, Wenzhou Medical University, Wenzhou, China; 8Department of Anesthesia and Critical Care, The Second Affiliated Hospital of Wenzhou Medical University, Wenzhou, China *These authors contributed equally to this work Background: The neutrophil–lymphocyte ratio (NLR) has been considered as an inflammatory marker in various disorders, but it is not clear whether the NLR is also elevated with hidden diabetes (HD), which is normal in fasting blood glucose (FBG) but abnormal in the oral glucose tolerance test (OGTT). Materials and methods: An HD animal model for 27 days and an animal model with oscillating glucose (OG) for 7 days were applied on adult female Sprague–Dawley rats. OGTT, leukogram analysis, histology, and immunohistochemistry were carried out. Results: In HD rats, the percentage of neutrophils increased but the percentage of lymphocytes decreased; hence, the NLR rose relative to sham. This may be a result of the OG levels often experienced by diabetic subjects, as normal rats given OG (6 g/kg/6 h) for 7 days had significantly reduced lymphocyte numbers and increased NLR compared with the values before and 1 h after oral glucose administration during OGTT. Glucose-induced disarrangement of partitions of circulating immune cells and NLR was involved in the increase in oxidative stress, as these changes were totally blocked by the antioxidant glutathione (GSH). GSH (50 mg/kg/6 h) totally blocked the glucose-induced alterations in lymphocyte and NLR values. Conclusion: HD associated with elevation of NLR values may be partly attributed to a homeostasis disorder of the innate inflammatory state, caused by oscillating hyperglycemia. Acute high glucose administration produced a significant decrease in lymphocyte number. OG administration potentiated this effect and increased the NLR value, which was blocked by GSH, suggesting that reactive oxygen species play a critical role in maintaining lymphocyte numbers. Keywords: neutrophil–lymphocyte ratio, diabetes, oscillating glucose level, innate immune, rat